Interdependence of selected stock market in Southeast Asia / Amirul Naim Azmi - Azmi, Amirul Naim (Faculty of Business and Management, 2020)
The aim of this study is to investigate the level of interdependence among selected stock market in Southeast Asia which are Malaysia stock market (KLSE), Singapore stock market (STI), Thailand stock market (SET), Philippines stock market (PSEI) and Indonesia stock market (JKSE). The monthly closing price of the stock market is from October 2009 to October 2019. From the result, it shows that Philippines stock market (PSEI) have strong association. However, for Malaysia stock market (KLSE) is the least stock market that associate with the other selected Southeast Asia stock market. Findings shows that there is weak correlation between Malaysia and the other selected Southeast Asia stock market from the period of October 2009 to October 2019. In terms of relationship, Philippines stock market seems have significant relationship with the Malaysia stock market, Singapore stock market, Thailand stock market and Indonesia stock market. On the other hand, Malaysia stock market have more insignificant relationship with Singapore stock market and Indonesia stock market while Singapore have insignificant relationship with Malaysia stock market and Thailand stock market. However, overall findings can conclude that there is no differences between the interdependence of Southeast Asia stock market.